ПУТЬ УЧЕНОГО - Джуанышбеков, Н. О. (Journal of Oriental Studies, 2016)
This article presents a study of the consequent trials of Omeyad khalifs and their governors to spread Islam in nowadays Central Asia (Transoxiania) especially during periods when their further invasion were stopped. Also the article discusses different religious movements that appear in that region and were based on moral tendencies and principles widely spread between inhabitants of those countries which joined above mentioned movements due to their bad social and economic mode of life.